Non random distribution of genomic features in breakpoint regions involved in chronic myeloid leukemia cases with variant t(9;22) or additional chromosomal rearrangements - Vicari Laura; Rossi Antonella; Casieri Paola; Coccaro Nicoletta; Zagaria Antonella; Anelli Luisa; Albano Francesco; Liso Vincenzo; Rocchi Mariano; Specchia Giorgina (Molecular Cancer, 2010)
Abstract Background The t(9;22)(q34;q11), generating the Philadelphia (Ph) chromosome, is found in more than 90% of patients with chronic myeloid leukemia (CML). As a result of the translocation, the 3' portion of the ABL1 oncogene is transposed from 9q34 to the 5' portion of the BCR gene on chromosome 22 to form the BCR/ABL1 fusion gene. At diagnosis, in 5-10% of CML patients the Ph chromosome is derived from variant translocations other than the standard t(9;22). Results We report a molecular cytogenetic study of 452 consecutive CML patients at diagnosis, that revealed 50 cases identifying three main subgroups: i) cases with variant chromosomal rearrangements other than the classic t(9;22)(q34;q11) (9.5%); ii) cases with cryptic insertions of ABL1 into BCR, or vice versa (1.3%); iii) cases bearing additional chromosomal rearrangements concomitant to the t(9;22) (1.1%). For each cytogenetic group, the mechanism at the basis of the rearrangement is discussed. All breakpoints on other chromosomes involved in variant t(9;22) and in additional rearrangements have been characterized for the first time by Fluorescence In Situ Hybridization (FISH) experiments and bioinformatic analyses. This study revealed a high content of Alu repeats, genes density, GC frequency, and miRNAs in the great majority of the analyzed breakpoints. Conclusions Taken together with literature data about CML with variant t(9;22), our findings identified several new cytogenetic breakpoints as hotspots for recombination, demonstrating that the involvement of chromosomes other than 9 and 22 is not a random event but could depend on specific genomic features. The presence of several genes and/or miRNAs at the identified breakpoints suggests their potential involvement in the CML pathogenesis.